Stability for grain yield in amaranth (Amaranthus hypochondriacus) - SHARMA, J K; LATA, S; SHARMA, R P (The Indian Journal of Agricultural Sciences, 2014)
The phenotypic stability of 8 genotypes of grain amaranth (Amaranthus hypochodriacus L.) grown during 1997, 1998 and 1999 was studied for 5 traits, viz days to maturity, plant height, panicle length, harvest index and grain yield. The genotypes performed differently during different years and showed significant genotype (G) X enviroment (E) interaction for all the traits. Both linear and non-linear components showed predominant G X E interaction for harves index; only linear component for days to maturity; and non-linear for plant height, panicle length and grain yield. ’Amont’ grain amaranth was stable with high mean performance for grain yield, harvest index and plant height, whereas ’Annapurna’ for grain yield and panicle length. Correlations among the 3 stability parameters could not observed.